Buried secrets - Finder, Joseph (New York : St. Martin's Press, 2011)
Hoping to set up his own spy operation in his Boston home town, Nick Heller is contacted by a desperate family friend to rescue his kidnapped daughter, whose terrifying incarceration in an underground crypt is being broadcast on the Internet.
National College of Business and Arts
Keywords: Kidnapping -- Fiction; Suspense fiction